Shifting pattern of gut microbiota in pregnant women two decades apart - an observational study - Rautava Samuli; Selma-Royo Marta; Oksanen Teo; Collado Maria Carmen; Isolauri Erika (TAYLOR & FRANCIS INC, 2025)
Background:
Past decades have witnessed a decrease in environmental biodiversity. We hypothesized a similar decrease in indigenous gut microbiota diversity, which may have contributed to the obesity epidemic.
Objective:
To investigate the changes in the composition and function of the gut microbiota in pregnant women over a period of 20 years.
Study design:
Altogether 124 pregnant women (41 overweight and matched 83 normal weight) pregnant in 1997, 2007 or 2017 were included in the study. The gut microbiota composition was assessed from fecal samples obtained at 32 weeks of gestation by 16S rRNA gene sequencing. Fecal short chain fatty acid (SCFA) profiles were measured by gas chromatography mass spectrometry (GC-MS).
Results:
Distinct gut microbiota profiles were detected in pregnant women from 1997, 2007 and 2017 (PERMANOVA Bray-Curtis R2 = 0.029, p = 0.001). The women pregnant in 1997 exhibited significantly higher microbiota richness and diversity as compared to those pregnant in 2007 and 2017. The total concentration of fecal SCFAs was significantly higher in the pregnant women in 1997 compared to those in 2007 and 2017. Significant differences in gut microbiota composition between normal weight and overweight women were manifest in 1997 but not in 2007 or 2017.
Conclusions:
The decrease in intestinal microbiota richness and diversity over two decades occurred in parallel with the decline in biodiversity in our natural surroundings. It appears that the gut microbiota of pregnant women has changed over time to a composition typical for overweight individuals.